Real-time determination of enantiomeric and isomeric content using photoelectron elliptical dichroism. Issue 1 (December 2018) - Comby, A.; Bloch, E.; Bond, C.; Descamps, D.; Miles, J.; Petit, S.; Rozen, S.; Greenwood, J.; Blanchet, V.; Mairesse, Y.
Abstract The fast and accurate analysis of chiral chemical mixtures is crucial for many applications but remains challenging. Here we use elliptically-polarized femtosecond laser pulses at high repetition rates to photoionize chiral molecules. The 3D photoelectron angular distribution produced provides molecular fingerprints, showing a strong forward-backward asymmetry which depends sensitively on the molecular structure and degree of ellipticity. Continuously scanning the laser ellipticity and analyzing the evolution of the rich, multi-dimensional molecular signatures allows us to observe real-time changes in the chemical and chiral content present with unprecedented speed and accuracy. We measure the enantiomeric excess of a compound with an accuracy of 0.4% in 10 min acquisition time, and follow the evolution of a mixture with an accuracy of 5% with a temporal resolution of 3 s. This method is even able to distinguish isomers, which cannot be easily distinguished by mass-spectrometry. The analysis of chiral chemical mixtures is crucial for many applications. Here, the authors perform real-time analysis of samples by ionizing them with elliptically polarized femtosecond laser pulses and detecting the angular distributions of the photoelectrons.